Laparoscopic Cholecystectomy for Symptomatic Cholecystic Disease in Children: Defining Surgical Timing - Pelizzo, Gloria; Bussani, Rossana; De Silvestri, Annalisa; Di Mitri, Marco; Rosone, Gregorio; Amoroso, Salvatore; Milazzo, Mario; Girgenti, Vincenza; Mura, Giovanni Battista; Unti, Elettra; Rozze, Davide; Shafiei, Vennus; et al. (Frontiers in Pediatrics, 2020)
Background: Laparoscopic cholecystectomy (LC) is the standard of care for gallbladder (GB) pathologies. We evaluated clinical, ultrasonographic (US) data as well as histopathological findings in children affected with symptomatic cholecystic disease (SCD) who underwent LC, with the aim of defining surgical timing. Methods: We reviewed our cases who underwent elective LC (ECL) or urgent LC (UCL). Clinical, US, surgical and histological features were used to create different risk scores. Results: We considered 26 children (17 ECL/9 ULC). US signs were not different in the two groups (p>0.05). Operating times were longer in ELC than in ULC (p=0.01). Histopathological evaluation revealed fibrosis and atrophy in both ELC and ULC. The clinical risk score was higher in ELC compared to ULC (p<0.001). An increased operative risk score was noted in patients with systemic inflammatory signs (OR1.98), lithotherapy (OR14.3) and wall thickening ≥3 mm (OR2.6). An increased histopathological risk score was detected in children with symptom duration >7 days (OR3.61), concomitant hematological disease (OR1.23) and lithotherapy (OR3.61). Conclusion Criteria adopted in adults cannot be adopted to detect the severity of GB damage in children. A dedicated clinical and US score is mandatory to define the most appropriate surgical timing.